Nonthyroid Metastasis to the Thyroid Gland: Case Series and Review with Observations by Primary Pathology. (22nd July 2016) - Russell, Jonathon O.; Yan, Kenneth; Burkey, Brian; Scharpf, Joseph
Abstract : Objective: Nonthyroid metastases to the thyroid gland can cause morbidity, including dysphagia, dysphonia, and airway compromise. Because metastatic malignancies portend a poor prognosis, obtaining equipoise between treatment morbidity and local disease progression is paramount. We reviewed cases of nonthyroid metastases to determine treatment and prognostic recommendations. Study Design: Case series with chart review. Setting: Tertiary care hospital. Subjects and Methods: We searched PubMed for reported cases between 1994 and September 2013 using search terms as follows: any combination of primary tumor locations and thyroid, as well as the terms thyroid and metastasis . Only unique cases of nonthyroid metastases were included. Combined with 17 additional tumors at our own institution, we found 818 unique nonthyroid metastases, of which 384 had management and survival data available. Results: Renal cell carcinoma was most common, presenting in 293 (35.8%) patients, followed by lung and gastrointestinal malignancies. Patients were treated with total thyroidectomy (34.0%), subtotal thyroidectomy including lobectomy (32.6%), and no surgery (33.5%). Surgical management was associated with improved survival duration ( P <. 01). Locoregional recurrence was less likely in patients treated with total versus partial thyroidectomy (4.8% vs 13%). Extent of surgical management did not have a significant effect on patient survival. Delayed presentation was associated with improved survival duration ( P =. 01). Conclusions: Nonthyroid metastases to the thyroid gland are unusual tumors. Surgical intervention is associated with improved survival, but expected morbidity of untreated tumors is difficult to assess. Site of origin, time to diagnosis, and surgical approach are related to survival and recurrence rates.